التسامح الفكري وعلاقته بالتماسك الاجتماعي لدى طلبة الجامعة - الجبوري, مناف فتحي عبد الرزاق (lark, 2019)
Abstract  This study aimed to identify the level of Tolerance among university students of Karbala and measure the level of tolerance  according to the gender (males _ females) , also  level of social Cohesion among the students of university , measure  the level of social  Cohesion  according to the gender (males _ females) and know the relationship between the Tolerance and  social  Cohesion .The sample consisted find applied of (50) students from college of education _ phase university of Karbala and for its departments (psychology , English , departments Arabic, history , geography) only for morning studies .In order to achieve object of the present research , the researcher prepared measure the Tolerance in the man , were verified honesty virtual two measure submitted with to (6) experts as a number of(18) pargraphs after it was  (42)  pargraph and the number of  pargraph of the seale of social  Cohesion  measure (72) pargraphs after it was (97) items . as well sa the extraction of stability of the two measure of tolerance stability of (0.64) in retail mid _ term has been to correlation coefficient person , as well the scule  social  Cohesion (0.72)  in Re_test  educational administ ration for one sample and tow sample and person correlation coefficient .The results of research were indicated , that are the students of the university don’t have tolerance and there were no statistically  significant differences among male and females in to tolerance , the students also have social  Cohesion and there were no statistically significant differences among male and females ,there is no statistically  significant relationship beteen the tolerance and social  Cohesion